Wyniki aplikacji metody składanek materiałów krzemiennych ze stanowiska Żuławka 13, gm. Wyrzysk, pow. pilski - Kaczor, Maciej (Folia Praehistorica Posnaniensia, 2018)
The article presents the results of the analysis of Świderian culture materials from Żuławka, site 13, com. Wyrzysk, with the refitting method applied. The refitting blocks have been analysed twice, from different points of view. The first study, in 2003, concentrated on spatial relations between areas of activities, while the second analysed technological aspects. The article aims to present unpublished results of the study.